Analisis Kandungan Zat Gizi Makro Biskuit Dengan Formulasi Tepung Ikan Lele Dan Tepung Kedelai Dalam Upaya Mencegah Stunting - Yuliana Salman; Siti Khadijah; Nany Suryani (HB PRESS, 2019)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that the child is too short from his age. The results of the Basic Health Research in 2018 showed the prevalence of stunting reaching 30.8%. Based on the results of Monitoring the Nutritional Status in 2017 in the province of South Kalimantan the prevalence of stunting was 34.2%. This prevalence rate has increased compared to the 2016 results of 31.1% while the WHO limit is <20%. Efforts to overcome nutritional deficiencies that occur in toddler need the Supplementary Feeding. The purpose of this study was to analyze the macro nutrient content of biscuits with catfish flour and soy flour formulations. This research is an experimental research with a completely randomized design with 4 formulations and 3 replications. The dependent variable in this study is the content of macro nutrients (carbohydrates, protein and fat), while the independent variables, namely the formulation of wheat flour, soy flour, catfish flour. Data analysis techniques used statistical analysis of variance analysis (one way ANOVA). The results showed the highest average carbohydrate content in the P0 formulation (control), namely 57.65%, the highest protein content in P3 formulation (25% catfish flour: 5% soy flour), which was 11.33%, while the highest fat content in P2 formulation(20% catfish flour: 10% soy flour), which is 19.65%. Based on statistical tests, it is proven that there are differences in the macro nutrients content (carbohydrates, proteins and fats) of biscuits to catfish flour and soy flour formulations. The best biscuit formulation in terms of macro nutrient content to stunting prevention efforts is P3 formulation (25% catfish flour: 5% soy flour).